INVESTIGATION OF EFFECT OF POLYMERS ON CALCIUM OXALATE CRYSTALLIZATION - Akin, Muhammed Bora; Bozkurt, Ayhan; Oner, Mualla (YILDIZ TECHNICAL UNIV, 2007)
In this study, the effects of additives on the crystallization of calcium oxalate have been investigated in aqueous solutions. Poly(Vinylphosphonic acid-co-4-Vinylimidazole), (Poly(VPA-co-4-VIm)), with different acid contents, Vinylphosphonic acid (VPA) and Ethylene glicol methacrylate phosphate ( EGMP) with different N, N-Methylene bis acrylamide (MBA) contents have been synthesized for using as additives. The effect of polymers on the rate of crystallization of calcium oxalate has been determined by recording the change of solution conductivity versus time. The polymer architecture and acid contents of the polymers were found to be important parameters in inhibition of calcium oxalate crystallization.
Keywords: Calcium oxalate; polyelectrolytes; crystallization; additives; Engineering